ANALISIS DETERMINAN KONSUMSI MASYARAKAT URBAN PROVINSI JAWA TENGAH - Fitrya Rahmawati (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2023)
Urban society in the modern era has turned into a consumer society which results in high levels of consumption signifying social success and individual happiness. Urban communities are also pressured by the need to shop continuously in order to appear in line with the times. This then encourages excessive consumption activities. This study aims to analyze the factors that affect the consumption of urban communities in Central Java. This study takes several consumption factors of urban society, namely population, GRDP, and the Minimum Minimum Wage for each city in Central Java Province. Secondary data is the source of data as well as the type of data, namely panel data from six cities in Central Java within a five-year period from 2016 – 2020. The panel data regression method produces an analysis that is not found to have a positive and significant effect on population and GRDP, while variables which has a positive and significant influence on public consumption in the cities of Central Java is only the UMK. Simultaneously the population, GRDP, and UMK affect the consumption of urban people in Central Java Province.